Footwear as a risk factor of hookworm infection in elementary school students - Semuel Sandy; Sri Sumarni; Soeyoko Soeyoko (Universa Medicina, 2014)
BACKGROUNDIn Indonesia, there is still a high prevalence of hookworm infection, especially in poor areas with poor sanitation. The number of helminthic diseases in Keerom Regency was about 599 cases in 2010. This number is bound to increase due to the low sanitation, hygiene and socio-economic status of the people in the regency. The children are a group at risk for contracting infections, especially intestinal worms, which affect the child’s physical growth and intelligence. The objective of this study was to determine the risk factors of hookworm diseases in elementary school students.METHODSA cross-sectional study was conducted on 224 elementary school students.Demographic data were obtained by questionnaire, comprising gender, parental socio-economic status, household sanitation, and personal hygiene. Body mass index was calculated by measurement of body weight and height. And hemoglobin concentration was measured using a Quick Check Hb-meter. Stool samples were microscopically examined using the Kato-Katz method. We used chi-square and logistic regression to find predictors of hookworm infections, with level of significance at p<0.05.RESULTSThe number of hookworm infection was 6.7% and the risk factor of hookworminfection among elementary school students was the habit of using footwearoutdoors [OR 5.3; 95% CI 1.7-17.7; p=0.004].CONCLUSIONThe use of footwear outdoors was a predictor of hookworm infections inelementary school children. An effective and efficient intervention program isneeded to prevent and eradicate hookworm infection among primary schoolchildren.